Corporate governance implementation on earnings management practices: Firm size as moderation - Soesetio, Yuli; Anggraeni, Cholifah Nur; Rudhiningtyas, Dyah Arini; Fuad, Muhammad (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
This study aims to analyze the effect of corporate governance, firm performance, and firm characteristics on earning management (EM). The data used in this study are secondary data, that is financial statements of non-financial companies listed on Indonesian Stock Exchange (IDX) in period 2010-2021 with a total sampel of 116 companies. Using multiple linear regression analysis pooled least square method, moderated regression analysis, and sub-group regressions prove that institutional ownership and board size as proxies for corporate governance affect earnings management practices (EM). Financial performance, which is proxied by return on assets (ROA) and sales growth (SGR) has a significant effect on EM. Through the moderation test, firm size (SIZE) as pure moderation. SIZE only perfoms as a moderator not as an independent variable that effects the relationship between board size (BZISE) and EM. In this study, profitability is the most dominant factor in determining EM. This study can provide useful information for shareholders and regulators in evaluating corporate governance attributes, financial performance and company characteristics that are effective in reducing EM practices. This study also contributes to the existing literature regarding EM practices, especially in non-financial companies listed on the IDX